f(x)= 4x^2 -2x +8 , g(x)= 4-x^2
I'm having a bit of an issue with this one: I understand how to get all of the answers except for when I hit the (f.g)(x) part. They are saying the answer is: -4x^4 + 2x^3 + 8x^2 - 8x + 32. I keep getting the numbers all wrong. Can anyone explain in steps to me how to figure this out? Thanks!
I'm having a bit of an issue with this one: I understand how to get all of the answers except for when I hit the (f.g)(x) part. They are saying the answer is: -4x^4 + 2x^3 + 8x^2 - 8x + 32. I keep getting the numbers all wrong. Can anyone explain in steps to me how to figure this out? Thanks!
-
f(x) = 4x^2 - 2x + 8 ; g(x) = 4 - x^2
(f.g)(x) = f(x).g(x)
= (4x^2 - 2x + 8)(4 - x^2)
= 4x^2(4 - x^2) - 2x(4 - x^2) + 8(4 - x^2)
= 16x^2 - 4x^4 - 8x + 2x^3 + 32 - 8x^2
= -4x^4 + 2x^3 + 16x^2 - 8x^2 - 8x + 32
= -4x^4 + 2x^3 + 8x^2 - 8x + 32
Just distribute the binomial on each term of the trinomial. That makes it much more easier.
And that's it. Hope I'm not too late.
(f.g)(x) = f(x).g(x)
= (4x^2 - 2x + 8)(4 - x^2)
= 4x^2(4 - x^2) - 2x(4 - x^2) + 8(4 - x^2)
= 16x^2 - 4x^4 - 8x + 2x^3 + 32 - 8x^2
= -4x^4 + 2x^3 + 16x^2 - 8x^2 - 8x + 32
= -4x^4 + 2x^3 + 8x^2 - 8x + 32
Just distribute the binomial on each term of the trinomial. That makes it much more easier.
And that's it. Hope I'm not too late.
-
For this problem you will need to do the "FOIL" Method.
(4x^2)(4)+(4x^2)(-x^2)+(-2x)(4)+(-2x)(…
After Foil you are left with
16x^2-4x^4-8x+2x^3+32-8x^2
Simplify and you get
-4x^4+2x^3+8x^2-8x+32
(4x^2)(4)+(4x^2)(-x^2)+(-2x)(4)+(-2x)(…
After Foil you are left with
16x^2-4x^4-8x+2x^3+32-8x^2
Simplify and you get
-4x^4+2x^3+8x^2-8x+32
-
x=potato